Identification and characterization of two wheat Glycogen Synthase Kinase 3/ SHAGGY-like kinases - Bittner, Thomas (BioMed Central, 2013)
BACKGROUND: Plant Glycogen Synthase Kinase 3/ SHAGGY-like kinases (GSKs) have been implicated in numerous biological processes ranging from embryonic, flower, stomata development to stress and wound responses. They are key regulators of brassinosteroid signaling and are also involved in the cross-talk between auxin and brassinosteroid pathways. In contrast to the human genome that contains two genes, plant GSKs are encoded by a multigene family. Little is known about Liliopsida resp. Poaceae in comparison to Brassicaceae GSKs. Here, we report the identification and structural characterization of two GSK homologs named TaSK1 and TaSK2 in the hexaploid wheat genome as well as a widespread phylogenetic analysis of land plant GSKs. RESULTS: Genomic and cDNA sequence alignments as well as chromosome localization using nullisomic-tetrasomic lines provided strong evidence for three expressed gene copies located on homoeolog chromosomes for TaSK1 as well as for TaSK2. Predicted proteins displayed a clear GSK signature. In vitro kinase assays showed that TaSK1 and TaSK2 possessed kinase activity. A phylogenetic analysis of land plant GSKs indicated that TaSK1 and TaSK2 belong to clade II of plant GSKs, the Arabidopsis members of which are all involved in Brassinosteroid signaling. Based on a single ancestral gene in the last common ancestor of all land plants, paralogs were acquired and retained through paleopolyploidization events, resulting in six to eight genes in angiosperms. More recent duplication events have increased the number up to ten in some lineages. CONCLUSIONS: To account for plant diversity in terms of functionality, morphology and development, attention has to be devoted to Liliopsida resp Poaceae GSKs in addition to Arabidopsis GSKs. In this study, molecular characterization, chromosome localization, kinase activity test and phylogenetic analysis (1) clarified the homologous/paralogous versus homoeologous status of TaSK sequences, (2) pointed out their affiliation to the GSK multigene family, (3) showed a functional kinase activity, (4) allowed a classification in clade II, members of which are involved in BR signaling and (5) allowed to gain information on acquisition and retention of GSK paralogs in angiosperms in the context of whole genome duplication events. Our results provide a framework to explore Liliopsida resp Poaceae GSKs functions in development.